Land use conflicts in Jelutong area of Georgetown, Malaysia: issues for sustainable urban development - Mohit, Mohammad Abdul; Raja Mohd Firdaus, Raja Mohd. Harun (Department of Urban & Regional Planning, Jahangirnagar University, 2006)
Land use conflits occurs as a consequence of incompatibility of land uses and when the market force alone determines the land uses of an urban area. This study intends to look at urban land use conflits in small area of Jelutong in georgetown, Malaysia. The study identified three cases of land use conflicts in the area. The first one was between industries and residential areas, the second case was between a factory and river reserve, and the third case was between a workshop and surrounding land uses. Based on the findings, the study identified the reasons for the occurrence of those conflicts. The study then developed five alternative approaches, with a recommendation to adopt concensus building as a policy approach to deal with the phenomena.